Análise do impacto do Programa Mais Médicos nos indicadores de morbimortalidade infantil na Paraíba entre 2013-2017 - Gomes, Adriana Nascimento (2021)
The Mais Médicos Program was implemented in Brazil in 2013, in priority municipalities, mainly in the North and Northeast regions, where there are micro-regions of extreme poverty and high vulnerability and scarcity of doctors, according to the classification profile. The program aims to increase and improve the supply and distribution of medical professionals at the primary care level of the Unified Health System. To this end, vacancies were created in new medical schools and Brazilian and foreign medical professionals were called on, on an emergency basis. This thesis aimed to analyze the impact of the Mais Médicos Program on child morbidity and mortality indicators in the municipalities of Paraíba between 2010 and 2017. An exploratory study with a mixed approach was carried out, comprising two phases of the study (qualitative and quantitative). In the qualitative approach, specialists who were involved with the PMM were consulted in order to investigate and know how the PMM was configured in Paraíba and to guide the research paths; two focus groups were held with the managers of the PMM State Coordination Commission in Paraíba as the objective. to analyze the changes in the provision of doctors in the state of Paraíba and the perceptions of the changes that occurred between 2018 and 2019. The content of the speeches was analyzed and listed in three thematic categories: Before and during: access and repercussions of the PMM; Governance; Structural changes in the provision of physicians. The quantitative approach was adopted in a quasi-experimental study, with 221 municipalities divided into two groups: control (cities that did not participate in the program) and intervention (cities that received the program). These groups were analyzed in two periods of program implementation: before (quadrennium 1, from 2010 to 2013) and after (quadrennium 2, from 2014 to 2017). The data analyzed by municipality were: density of equivalent physicians in primary care, rate of hospitalization by condition sensitive to primary care in children under five years old, infant mortality rate and mortality rate in children under five years old. In the statistical analysis, non-parametric tests were used, due to the non-normal distribution of sample data. To compare the groups of municipalities with and without the program, the test for samples independent of the sum of ranks (Mann-Whitney test) was used. Regarding paired samples, the test used was the Wilcoxon to analyze the variables before and after the program. The municipalities were stratified according to the three health macro regions Paraíba. A significance level of 5% was adopted in all analyses. Based on the hypothesis tests, a Decision Model based on rules was created to explain the effect of the PMM (positive or negative). from Paraíba, with a negative evaluation of the departure of Cuban doctors after the end of cooperation between Cuba and Brazil and the non-renewal of the Program in the metropolitan regions, leaving huge care gaps. The dismantling of the PMM was feared, without the prospect of effective alternatives to the provisioning program. In Paraíba (n=221), between the two quadrenniums analyzed, there was an increase of 2.6% in the density of primary care physicians, with an increase of 4% in the municipalities of the PMM throughout the state and of 6.8% in this same group in the 3rd health macro-region. There was a 16% decrease in the rate of admissions for sensitive conditions in primary care in the State, with a reduction of 18% in the municipalities of the PMM. The reduction in the infant mortality rate in children under one year of age in Paraíba was 12.4%; in the municipalities of the PMM the reduction was slightly greater (15.3%), this effect was observed in the 1st and 3rd health macro-regions, with a reduction of 12.2% and 20.8%, respectively. There was a significant reduction of 10.4% in the mortality rate in children under five in all municipalities, with a greater reduction (10.8%) in the municipalities of the PMM and in the 1st (15.9%) and in the 3rd (18% ) health macro-region. The Decision Model proposed in this thesis indicates, for health managers and decision makers, that municipalities that joined the Mais Médicos Program had a reduction in admissions for conditions sensitive to primary care in children under five years of age, infant mortality and mortality in children under five years of age in Paraíba, mainly in municipalities in regions with greater health needs, such as the Sertão nordestino, contributing to the reduction of health inequalities and guaranteeing the basic right to health care and life for this population.